In vivo and in vitro studies on fluorophore-specificity - Kolbert, Zsuzsanna (Acta Biologica Szegediensis, 2012)
In vivo and in situ microscopy is a selective and easy method for detecting reactive oxygen (ROS)- and nitrogen species (RNS). Of the several fluorescent indicators developed in the last 30 years, the specificity and sensitivity of 4-amino-5-methylamino-2’-7’-difluorofluorescein diacetate (DAF-FM DA) as a nitric oxide (NO) indicator was tested by spectrofluorimetry and fluorescence microscopy. The peroxynitrite (ONOO-)-dependence of aminophenyl fluorescein (APF) and the hydrogen peroxide (H2O2)-sensitivity of 2’-7’-dichlorodihydrofluorescein diacetate (H2DCF DA) and 10-acetyl-3,7-dihydroxyphenoxazine (Amplex Red) was also determined. The results show that DAF-FM is a suitable fluorophore for detecting NO in plant tissues and aminophenyl fluorescein can be used as a ONOO- -responsive dye. It was also found that DCF does not detect NO in solutions, but its fluorescence emission is strongly sensitive to H2O2. Moreover, the DCF fluorescence was found to be ONOO—sensitive, as well. In vivo studies revealed that Amplex Red can be applied as a H2O2-sensitive and -selective fluorophore in plant tissues.